Organising food differently: Towards a more-than-human ethics of care for the Anthropocene. (July 2018) - Beacham, Jonathan
In this article, I consider how organisations within 'Alternative' Food Networks might help us to enact a more-than-human ethic of care in the Anthropocene. Drawing on the diverse economies framework of J.K. Gibson-Graham (2006a, 2006b) as well as readings in the feminist ethics of care literature, I explore an ethnographic study of three community supported agriculture schemes in the north-west of England. While there has been surprisingly little scholarly work linking food and the Anthropocene, much more has been made of the relationship between the food system and Anthropogenic processes of climate change. The orthodox responses to the problems that climate change may bring about are undergirded by Hobbesian visions and the perceived viability of instrumental, technocratic 'fixes' that are, for many reasons, worthy of critique. Broadening our viewpoint, and recognising that the Anthropocene and climate change require different responses, I argue that AFNs can provide a more hopeful perspective in how we might understand our existence within a more-than-human world. Rather than reading AFNs through analytical binaries as either reformist or radical entities merely confronting the ills of the food system, I develop an account that instead understands them as open-ended and tantalisingly different forms of organisation (Stock et al., 2015b) that can play a central role in fostering a more-than-human ethics of care for the Anthropocene.